PENERAPAN METODE SAM’IYAH WA SYAFAWIYAH (MENDENGAR DAN MENGUCAPKAN) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BAHASA ARAB SISWA KELAS VII B SEMESTER GENAP DI MTs MATHLA’UL ANWAR TEMPEL REJO KEDONDONG– PESAWARAN TAHUN PELAJARAN 2009-2010 : PENERAPAN METODE SAM’IYAH WA SYAFAWIYAH - Ahmad Hadi Setiawan; Muhammad Irham (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2018)
Some of the obstacles commonly faced by Arabic language teachers are the low activity and student learning outcomes. These constraints occur because students are less involved in the learning process. Sam'iyah wa syafawiyah (listening and speaking) methode is a learning method that focuses on listening and speaking competencies in the initial learning process, then refined with four other competencies (listening, speaking, reading, and writing). So that the application of these methods is expected to be able to create experiences and good learning outcomes. The formulation of the problem in this research is: Whether through the application of the sam'iyah wa syafawiyah method (listening and speaking) can improve the activities and learning outcomes of Arabic students of class VII B in the even semester at MTs. Mathla'ul Anwar Tempel Rejo Kedondong? Research subjects were students of class VII B in the even semester at MTs. Mathla'ul Anwar Tempel Rejo Kedondong in the 2009-2010 Academic Year, amounting to 31 people consisting of 12 male students and 19 female students. The research was conducted in three cycles consisting of four meetings in each cycle. Based on the research conducted obtained the results: (1) There is an increasing in the average value of student learning activities during learning with the sam'iyah wa syafawiyah method, namely: 67.75% at the time of the pre-test increased to 91.40% at the time of the post-test, while in the first cycle of 76.89% to 78.16% in the second cycle and 86.48% in the third cycle. (2) The average value of students' Arabic learning outcomes has increased in each cycle, namely: 43.87 at the time of the pre-test increased to 78.71 at the time of the post-test, while at the time of the first cycle test of 59.68 increased to 68.39 in the second cycle and 89.52 in the third cycle. The results of this research indicate that the expected indicators of success have been met, and in general the application of the sam'iyah wa syafawiyah method can improve the activities and learning outcomes of Grade VII B Arabic students in the even semester at MTs. Mathla'ul Anwar Tempel Rejo Kedondong in 2009-2010 Academic Year.